Evaluation of Duodenal Hypersensitivity to Acid Using Transnasal Endoscopy - Ishii, Manabu; Kusunoki, Hiroaki; Manabe, Noriaki; Kamada, Tomoari; Tarumi, Ken-ichi; Matsumoto, Hiroshi; Sato, Motonori; Yamanaka, Yoshiyuki; Murao, Takahisa; Tsutsui, Hideaki; Shiotani, Akiko; Hata, Jiro; et al. (IntechOpen, 2011)
None